2019
DOI: 10.3389/fchem.2019.00136
|View full text |Cite
|
Sign up to set email alerts
|

Iron Redox Speciation Analysis Using Capillary Electrophoresis Coupled to Inductively Coupled Plasma Mass Spectrometry (CE-ICP-MS)

Abstract: Neuronal iron dyshomeostasis occurs in multiple neurodegenerative diseases. Changes in the Fe(II)/Fe(III) ratio toward Fe(II) is closely related to oxidative stress, lipid peroxidation, and represents a hallmark feature of ferroptosis. In particular for body fluids, like cerebrospinal fluid (CSF), reliable quantitative methods for Fe(II)/(III) redox-speciation analysis are needed to better assess the risk of Fe(II)-mediated damage in brain tissue. Currently in the field of metallomics, the most direct method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In line with this, only BNIP3‐depleted cells—but not autophagy‐compromised cells—displayed a significantly higher content of intracellular Fe 2+ as imaged and quantitated by FerroOrange, a probe reacting specifically with intracellular Fe 2+ ions (Fig 6A). Furthermore, to validate this finding we performed highly sensitive capillary electrophoresis combined with inductively coupled plasma mass spectrometry(CE‐ICP‐MS), from shCntl, shBNIP3, and shATG5 melanoma cells, which allowed for quantitative Fe 2+ /Fe 3+ speciation analysis (Michalke et al, 2019). This analysis showed that while the total iron content across these cell lines remained constant (Fig 6B; Appendix Table S3), shBNIP3 cells harbored a significantly higher proportion of Fe 2+ when compared to Fe 3+ (Fig 6B, Appendix Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, only BNIP3‐depleted cells—but not autophagy‐compromised cells—displayed a significantly higher content of intracellular Fe 2+ as imaged and quantitated by FerroOrange, a probe reacting specifically with intracellular Fe 2+ ions (Fig 6A). Furthermore, to validate this finding we performed highly sensitive capillary electrophoresis combined with inductively coupled plasma mass spectrometry(CE‐ICP‐MS), from shCntl, shBNIP3, and shATG5 melanoma cells, which allowed for quantitative Fe 2+ /Fe 3+ speciation analysis (Michalke et al, 2019). This analysis showed that while the total iron content across these cell lines remained constant (Fig 6B; Appendix Table S3), shBNIP3 cells harbored a significantly higher proportion of Fe 2+ when compared to Fe 3+ (Fig 6B, Appendix Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Cell lysates were centrifuged at 10,000 g for 10 min, and supernatants were sent on dry ice to Helmholtz Center Munich. Speciation and quantification of Fe 2+ , Fe 3+ , and total iron were performed by capillary electrophoresis inductively coupled plasma mass spectrometry (CE‐ICP‐MS) as described previously (Michalke et al, 2019). Briefly, samples were analyzed on a "PrinCe 706” CE system equipped with an uncoated capillary (85 cm × 50 µm ID) and a laboratory‐constructed CE‐ICP‐MS interface for element selective iron quantification of separated iron redox species at ICP‐DRC‐MS.…”
Section: Methodsmentioning
confidence: 99%
“…More work is needed to directly measure iron burden in FTL positive microglia from brains with and without neurodegenerative pathology. For instance, Fe(II) and Fe(III) could be measured on FACS sorted microglia from the postmortem tissue using capillary electrophoresis coupled-to-inductively-coupled plasma mass spectrometry (CE-ICP-MS)[35].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of liver iron content (LIC). Total liver iron was quantified by using the ferrozine assay (11) or inductively coupled plasma mass spectrometry (ICP-MS) (38).…”
Section: Quantification Of Serum Non-transferrin Bound Iron (Ntbi) Ntbi Was Measured Bymentioning
confidence: 99%